2021
DOI: 10.1172/jci.insight.141420
|View full text |Cite
|
Sign up to set email alerts
|

Role of MIF in coordinated expression of hepatic chemokines in patients with alcohol-associated hepatitis

Abstract: Background: The chemokine system of ligands and receptors is implicated in the progression of Alcohol-associated hepatitis (AH). Finding upstream regulators could lead to novel therapies. Methods: The coordinated expression of chemokines in livers of healthy controls (HC) and patients with AH in two distinct cohorts of patients with various chronic liver diseases. Studies in cultured hepatocytes and in tissue-specific knockouts were used for mechanistic insight into a potential upstream regulator of chemokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…233 It is an integral component of the host antimicrobial alarm system and stress response that induces the proinflammatory functions of immune cells. 232,[234][235][236] Recent studies report higher circulating and hepatic expression of MIF in ALD patients and EtOH-fed rodents. [236][237][238][239] Others report that MIFdeficient mice are more resistant to ALD development.…”
Section: Potential New Therapies and Targets For Ald Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…233 It is an integral component of the host antimicrobial alarm system and stress response that induces the proinflammatory functions of immune cells. 232,[234][235][236] Recent studies report higher circulating and hepatic expression of MIF in ALD patients and EtOH-fed rodents. [236][237][238][239] Others report that MIFdeficient mice are more resistant to ALD development.…”
Section: Potential New Therapies and Targets For Ald Treatmentmentioning
confidence: 99%
“…232,[234][235][236] Recent studies report higher circulating and hepatic expression of MIF in ALD patients and EtOH-fed rodents. [236][237][238][239] Others report that MIFdeficient mice are more resistant to ALD development. These findings indicate that MIF-directed therapies may likely offer new treatment opportunities for ALD.…”
Section: Potential New Therapies and Targets For Ald Treatmentmentioning
confidence: 99%
“…The administration of a short lipopeptide (i.e., pepducin ′x1/2pal-i1′) that targets CXCR1/2 markedly attenuated fully established ALD in mice [ 193 ], thus showing the potential of CXCR1/2 blockade for the treatment of ALD. Likewise, the gene expression and serum levels of CCL20, the only chemokine ligand of CCR6, strongly correlated with the severity of AH and gene silencing, significantly ameliorated lipopolysaccharide (LPS)-induced inflammation and liver injury [ 192 , 199 ]. Given the contribution of chemokine–chemokine receptors toward the inflammatory milieu, numerous other chemokines may also participate in the pathogenesis of ALD including CXCL5, CXCL6, Gro-α, and IL-18, establishing their potential value as new biomarkers and/or therapeutic targets for ALD [ 11 , 20 , 191 , 200 ].…”
Section: Therapeutic Options For Various Stages Of Aldmentioning
confidence: 99%
“…Despite chemokines being intrinsic to immune cell/leukocyte trafficking and inflammation, they are produced by a spectrum of cells within the liver, from resident macrophages to non-immune hepatic epithelial cells like hepatocytes, sinusoidal epithelial cells, cholangiocytes, as well as HSCs and fibroblasts ( 10 ). Preclinical experimental models of liver injury show that most cell types can express and release chemokines in an attempt to resolve cellular injury or toxic insult ( 9 , 17 , 18 ).…”
Section: Chemokine Biology: Structure and Familiesmentioning
confidence: 99%
“…An atypical chemokine is included in this list, macrophage migration inhibitory factor (MIF) ( 30 , 31 ). MIF is a pleiotropic cytokine/chemokine which can interact with CXCRs to promote leukocyte chemotaxis, but our understanding of MIF’s role in liver disease has evolved over the past decade of research ( 18 , 32 36 ). The role of MIF in fibrosis is somewhat controversial, as studies in genetic knockout models reported contrasting roles for MIF in fibrosis.…”
Section: Chemokine Biology: Structure and Familiesmentioning
confidence: 99%